Self-reported Symptoms of Anxiety in a Sample of Public versus Private Secondary School Students in a District in Southwest Nigeria - Fakunmoju, Sunday B. (Technium Social Sciences Journal, 2023)
Few studies have examined the symptoms of anxiety among students in Nigeria. This article describes the prevalence, severity, and gender differences in symptoms of anxiety, as well as factors that engender fear and anxiety among public versus private secondary school students in Nigeria. A convenience sample of 502 students from three private and five public secondary schools in southwest Nigeria completed a questionnaire and anxiety scale in the classroom. Findings show that symptoms of obsessive-compulsive disorder (n = 104, 20.7%) and fear of physical injury (n = 60, 12%) were the most and least frequently reported, respectively. Similarly, public school students were more likely than private school students to report symptoms of anxiety. From the qualitative responses, fear and anxiety about the future and academic pressure (n = 27, 24.3%) emerged as the major thing students were really afraid of. More female and public-school students reported being anxious about many things than their male and private school counterparts. Identifying symptoms of anxiety among students is critical to determining educational policies for improving their educational outcomes. Understanding school differences in symptoms of anxiety may help bridge the gap in learning outcomes among students in private and public schools.